Implementation of Certification of Processing Feasibility (CPF) of Processed Milkfish Products in Indonesia - Pujiono Pujiono; Dewi Sulistianingsih; Laga Sugiarto (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2018)
Globalization gives businesspeople opportunities to expand their marketing areas. However, it also triggers competitions among the businesspeople of either big, medium, small, or micro enterprises. It also impacts fisheries businesspeople, especially those belonging to small and micro enterprises since they mostly still apply traditional equipment when processing their fish or processed fish products. The application of the traditional equipment leads to the low product quality. The low quality of their fish or processed fish products induces some worries of the perishing fisheries business in Indonesia. Certification of Processing Feasibility (CPF) of fisheries and processed fish products is a means to improve fish and processed fish product quality. The implementation of the certification emerges a dilemma among the small and micro enterprises whose capital and human resources are limited. Therefore, to overcome the problem it necessary that there are some policies to protect and develop the businesses of the small and micro enterprises. The necessary policies can be in the form of business empowerment through partnerships using inti-plasma pattern.